Intelligence and Cultural Differences: A Study of Cultural Learning and Problem-solving. - Tarver, James D. (Southwestern Social Science Quarterly, 1952)
Reviews the book "Intelligence and Cultural Differences: A Study of Cultural Learning and Problem-Solving," by Kenneth Fells.